Multi-scale functional and taxonomic β-diversity of the macroinvertebrate communities in a Mediterranean coastal lagoon - CABANA, D.; NICOLAIDOU, A.; SIGALA, K.; REIZOPOULOU, S. (Mediterranean Marine Science, 2017)
Benthic macroinvertebrate communities form the basis of the intricate lagoonal food web. Understanding their functional and taxonomic response, from a β-diversity perspective, is essential to disclose underlying patterns with potential applicability in conservation and management actions. Within the central lagoon of Messolonghi we studied the main environmental components structuring the macroinvertebrate community. We analyzed the β-taxonomic and β-functional diversity across the main habitats and seasons, over a year time frame. Our results outline habitat type and vegetation biomass as the major factors structuring the communities. We found environmental variability to have a positive correlation with functional β-diversity, however no correlation was found with taxonomic β-diversity. Across the seasons an asynchronous response of the functional and taxonomic β-diversity was identified. The taxonomic composition displayed significant heterogeneity during the driest period and the functional during the rainy season. Across the habitats the unvegetated presented higher taxonomic homogeneity and functionally heterogeneity, contrary the vegetated habitats present higher taxonomic variability and functional homogeneity. Across the seasons and habitats a pattern of functional redundancy and taxonomic replacement was identified. Besides high functional turnover versus low taxonomic turnover was documented in an anthropogenic organically enriched habitat We conclude that habitats display independent functional and taxonomic seasonal patterns, thus different processes may contribute to their variability. The framework presented here highlights the importance of studying both β-diversity components framed in a multiscale approach to better understand ecological processes and variability patterns. These results are important to understand macroinvertebrate community assembly processes and are valuable for conservation purposes.